Judge Muhammad bin Imran al-Taymi and his role In Islamic judiciary (130-154 AH / 748-769 AD) (Journal of the College of Basic Education, 2023)
Praise be to God, Lord of the worlds, and prayers and peace be upon the Seal of the Prophets and Messengers, our Master Muhammad, and upon his family and companions altogether, and whoever follows his guidance until the Day of Judgment and after.The most important pillars of happiness that humans seek is to reassure people of their rights, and to establish justice among them, and we hardly know anything that is more healing and strife, and purer to tranquility and stability between individuals and groups than the deprivation of rights, and the domination of the mighty over the peaceful Muslims.Therefore, the urgent need and the human need for the judiciary was a plot of justice to cut off the needles of sedition and eliminate all these corrupt phenomena that threaten security, peace and life.And the judiciary is one of the sacred matters for all nations, regardless of their degree of sophistication and civilization, as in the Almighty’s saying (And had it not been for God pushing people one by another, the earth would have been corrupted) (1)In order to achieve the aforementioned, the Arab Islamic State derived its laws from the tolerant Islamic Sharia, and paid attention to the judiciary, so it was keen on its independence.And since judgment and the judiciary are the arm of justice and the mirror in which all actions that are in need of justice and the highest degrees of reward are reflected, deriving the work from the Almighty’s word: “And if you judge, then judge between them with justice, for God loves those who are just.” (2)That is why Judge Muhammad bin Imran al-Taymi used to say: “By God, I am not frozen in the truth and I do not dissolve in falsehood.” What he means is that he judges with truth because the truth has life, and it is one of the names of God from whom and to whom everything in life is.